Experimental study on combustion and emission of an SI engine with ethanol /gasoline combined injection and EGR. (10th January 2022) - Zhao, Zhe; Yu, Xiumin; Huang, Yan; Shi, Weibo; Guo, Zezhou; Li, Zhe; Du, Yaodong; Jin, Zhaohui; Li, Decheng; Wang, Tianqi; Li, Yinan
Abstract: Ethanol is a widely used alternative fuel for sustainable development, showing potential for improving the combustion and emission characteristics. Both EGR and lean burn are important technical approaches for engines to reduce emissions In this paper, the performance EDI + GPI four-cylinder spark ignition engine at three access air ratios, five ethanol direct injection ratios and five exhaust recirculation ratios was studied at the speed of 1500rmp. The results show that, the cooperation of EDI and EGR can improve the engine performance. Under lean burn conditions, When 6%EGR+45%EDIr, CA 0-10 decreases 49. 8%. When 12%EGR+30%EDIr, BMEP increases 6. 59%, HC decreases 28.33%, total particle number decreases 93.87%. When 6%EGR+30%EDIr, Pmax increases 26.58%, crank angle corresponding to Pmax decreases 41.98%. And in this condition, CoVIMEP is only 1.46%, decreased 21.51% from the original engine. With the increase of λ, EGR limit of CO moves from 12% to 6%; the optimal ethanol direct injection ratio of CO moves from 30% to 15%. NOx decreases about 136.08 ppm with an average increase of 1% EGR. In summary, ethanol has a higher oxygen content and laminar flame speed is faster. EGR can not only reduce pumping losses and throttling losses, but also effectively accelerate the positive effects of ethanol on combustion and emissions. EGR + EDI + GPI can obviously increase the engine power performance, improve fuel economy and decline the emissions. When the engine speed = 1500 rpm, 12%EGR+30%EDIr is the optimal combination of SI engine at λ  = 1.2. Highlights: Most researches on combination of EGR and ethanol have been done on diesel engines. However, this test was carried out on combined injection four-cylinder SI engine, which can simultaneously achieve ethanol direct injection (EDI) plus gasoline port injection (GPI). This paper research a combustion system of exhaust gas recirculation (EGR) plus ethanol direct injection (EDI), and summarizes the optimal combination ratio of EGR + EDI and analyzes the interaction between EGR and ethanol. EGR + EDIr + GPI can obviously increase the engine power performance, improve fuel economy and decline the gaseous emissions. Most studies are conducted on the normal working condition of λ  = 1. This paper obtains the best method of ethanol and gasoline combined injection under lean burn condition, and analyzes the characteristics of the engine at 12%EGR+30%EDIr and λ  = 1.2.